PERAN UNITED NATION HIGH COMMISSIONER FOR REFUGEES DALAM MENANGANI PENGUNGSI SURIAH DI LEBANON TAHUN 2011-2016 - Nasution, Muhammad Rifai; Fachri, Yuli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research explains the role of international organizations in dealing with refugees as happened in Syria in 2011. One of the Syrian refugee destination countries is Lebanon, because it borders on Syria. The United Nations High Commissioner for Refugees (UNHCR), which has the task of coordinating protection and solutions for refugees in accordance with the mandate given by the United Nations in the name of humanity.This research uses qualitative research method. Data obtained from books, journals, articles, dictionaries and websites. The concept used in this research is the role concept and using the theory of international organization.This research shows the role of UNHCR in dealing with Syrian refugees and has made UNHCR an active role in providing its assistance to Syrian refugees residing in Lebanon. With UNHCR's collaboration with the Lebanese government a direct positive impact on Syrian refugees through continuous protection assistance, safety assistance and other assistance.Keywords: UNHCR, Role, Lebanon, and Syrian Refugees